Rehabilitacja neurologiczna pacjentki po udarze mózgu - opis przypadku = Neurological rehabilitation of a patient after stroke - case report - Dorota Ratuszek-Sadowska; Mikołaj Kowalski; Kamila Woźniak; Bartosz Kochański; Wojciech Hagner (Kazimierz Wielki University, 2016)
Ratuszek-Sadowska Dorota, Kowalski Mikołaj, Woźniak Kamila, Kochański Bartosz, Hagner Wojciech. Rehabilitacja neurologiczna pacjentki po udarze mózgu - opis przypadku = Neurological rehabilitation of a patient after stroke - case report. Journal of Education, Health and Sport. 2016;6(8):28-40. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59685 http://ojs.ukw.edu.pl/index.php/johs/article/view/3725       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     Rehabilitacja neurologiczna pacjentki po udarze mózgu - opis przypadku   Neurological rehabilitation of a patient after stroke - case report   Dorota Ratuszek-Sadowska1, Mikołaj Kowalski1, Kamila Woźniak2, Bartosz Kochański1, Wojciech Hagner1 1.         Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2.         Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu     Streszczenie Udary mózgu stanowią najczęstszą przyczynę trwałej niepełnosprawności, prowadząc do utraty zdolności aktywnego życia. Terapia neurologiczna pacjentów po przebytym udarze jest głównie ukierunkowana na największy możliwy wzrost funkcji. Podczas terapii stosowane są różne techniki mające na celu hamowanie patologicznych wzorców ruchowych, a także stymulację reakcji o charakterze fizjologicznym. Celem niniejszej pracy jest omówienie, na podstawie zaprezentowanego przypadku, postępowania rehabilitacyjnego u 29-letniej pacjentki po udarze niedokrwiennym prawej półkuli mózgu w przednim obszarze unaczynienia. Badanie fizjoterapeutyczne, opierające się na Międzynarodowej Klasyfikacji ICF, oceniające zaburzenia w obrębie struktur ciała, funkcji oraz aktywności i uczestnictwa, wykazało osłabienie mięśni dolnego tułowia, dna miednicy oraz lewego biodra, hipotonię mięśniową strony bezpośrednio zajętej, a także zwiększone napięcie mięśniowe dystalnie w lewej kończynie górnej. Problemami pacjentki na poziomie aktywności było samodzielne wstawanie i stanie bez asekuracji oraz brak aktywności kończyny górnej lewej. Prowadzona terapia obejmowała regulacje napięcia mięśniowego, pracę nad wzmocnieniem mięśni tułowia lewego biodra oraz miednicy, torowanie prawidłowego obciążania strony bezpośrednio zajętej podczas zmian pozycji z siadu do stania oraz chodu, a także naukę czynności dnia codziennego.   Słowa kluczowe: udar mózgu, rehabilitacja, terapia neurologiczna, ICF.   Abstract Stroke is the most common cause of permanent disability, leading to loss of active life. Neurological therapy of the patients after stroke is mainly aimed at the greatest possible growth of the function. During the treatment there are various techniques designed to inhibit pathological movement patterns, as well as the stimulation of a physiological response. The aim of this paper is to discuss, on the basis of the presented case, rehabilitation methods of 29-year-old patient after ischemic stroke of the right hemisphere of the brain in the front area of the vasculature. The physiotherapy examination, based on the International Classification of ICF, assessing problems in the body structures, functions and activities and participation, showed a weakness of the lower trunk muscles, pelvic floor and left hip, muscles hypotonia of directly occupied side, as well as increased muscle tension in left upper limb. Problems of patient activity levels were independent standing up and able to stand without help and lack of left upper limb function activity. Neurological therapy included the muscle tone normalization, work on strengthen core, left hip and pelvis muscles, priming the correct loading of the directly occupied side during the position changes from sitting position to standing and walking, as well as learning of daily living activities.   Key words: stroke, rehabilitation, neurological therapy, ICF.